Modelling Coaxial SHORT and OPEN Calibration Standards - Ung, Daniel (2023)
This paper explores the mathematical model used for calculating the reflection coefficient of a 3.5 mm offset coaxial SHORT and OPEN standard. The mathematical model uses physical properties and dimensions of the standard in order to calculate the response across frequency. To validate the theory presented, the standards were modelled using electromagnetic simulation software to obtain the reflection coefficients for comparison. The resulting difference in the phases between theoretical calculation and simulation results shows excellent agreement with a difference (Δ) less than 0.01° and 0.06° degrees for the SHORT and OPEN standard respectively over the frequency range of 10 MHz –25 GHz.